Medical Cross-Sectional Research Design - İRDAY, Kübra (MAS Journal of Applied Sciences, 2024)
Cross-sectional studies are conducted at a single point in time or over a short period of time. They are usually conducted to estimate prevalence for a particular population. In addition to relevant information, data on individual characteristics, including exposure to risk factors, can also be collected. In this way, cross-sectional studies provide a ’snapshot’. In a cross-sectional study design, the aim of the study is to find the prevalence of the outcome of interest for the population or subgroups within the population at a specific time point. They are easy to conduct and are the most common study designs reported in most medical journals. The research can be completed in a relatively short time, depending on the required sample size and access to the study population. Cross-sectional studies are extensively employed in epidemiology as well as other research fields. Cross-sectional studies are usually carried out by having participants complete a questionnaire. There are differences: occasionally the interviewer will pose the questions and record the responses from the participants. Respondents occasionally use a computer or the internet to complete the answers. Survey participants occasionally provide a blood sample or other biological measurement in addition to their questionnaire responses.